Phylogenetic characterization of rhinoviruses from infants in Sarlahi, Nepal. Issue 12 (21st August 2019) - Kuypers, Jane; Perchetti, Garrett A.; Chu, Helen Y.; Newman, Kira L.; Katz, Joanne; Khatry, Subarna K.; LeClerq, Steven C.; Jerome, Keith R.; Tielsch, James M.; Englund, Janet A.
Abstract: Problem: Rhinoviruses (RVs), the most common causes of acute respiratory infections in young children and infants, are highly diverse genetically. Objective: To characterize the RV types detected with respiratory illness episodes in infants in Nepal. Study methods: Infants born to women enrolled in a randomized trial of maternal influenza immunization in rural, southern Nepal were followed with household‐based weekly surveillance until 180 days of age. Infants with respiratory symptoms had nasal swabs tested for twelve respiratory viruses. A subset with RV alone was selected for sequencing of the VP4/2 gene to identify RV types. Results: Among 547 RV‐only positive illnesses detected from December 2012 to April 2014, 285 samples (52%) were sequenced. RV‐A, B, and C species were detected in 193 (68%), 18 (6%), and 74 (26%) specimens, respectively. A total of 94 unique types were identified from the sequenced samples, including 52 RV‐A, 11 RV‐B, and 31 RV‐C. Multiple species and types circulated simultaneously throughout the study period. No seasonality was observed. The median ages at illness onset were 88, 104, and 88 days for RV‐A, B, and C, respectively. The median polymerase chain reaction cycle threshold values did not differ between RV species. No differences between RV species were observed for reported respiratory symptoms, including pneumonia, or for medical care‐seeking. Conclusions: Among very young, symptomatic infants in rural Nepal, all three species and many types of RV were identified; RV‐A was detected most frequently. There was no association between RV species and disease severity. Highlight: RV infections were common among infants less than six months old in southern Nepal. All three species and 94 types of RV were identified by sequencing the VP4/2 gene. Multiple species and types circulated simultaneously throughout the study period. No symptomatic differences between RV species or types were observed.